Health Referral Enterprise Architecture Design in Indonesia - Putu Wuri Handayani; Ave Adriana Pinem; Qorib Munajat; Fatimah Azzahro; Achmad Nizar Hidayanto; Dumilah Ayuningtyas; Arief Sartono (Healthcare Informatics Research, 2019)
ObjectivesIn this study an enterprise architecture (EA) was developed for a health referral information system (HRIS) for individual healthcare in Indonesia with reference to the Open Group Architecture Framework (TOGAF) 9.1. The HRIS includes patient referrals for vertical and horizontal references (internal and external), specimen referrals, and health personnel referrals.MethodsThis research was a qualitative study that used the interview and observation method of the Primary Health Care Information System (SIMPUS) application developed by the Agency for Assessment and Application of Technology (BPPT). The interviews were conducted at South Tangerang City Government Health Office with five resource persons who were responsible for conducting health referral processes.ResultsThe EA of the HRIS includes the principles of architecture, business, application, data, and technology architecture. Twelve principles, four referral processes, and three application reference modules and centralized applications comprise the architecture of the HRIS. The HRIS is a centralized integrated application that uses application program interface (API) to integrate with SIMPUS.ConclusionsThe proposed architecture was developed in an integrated and comprehensive manner for the individual healthcare referral process, which can be implemented by regulators and healthcare facilities. This architecture can also help regulators and healthcare facilities to standardize and integrate health referral data and related processes.